Lukova Cave in the Kolpa valley, Slovenia. A new archaeological and palaeontological site - Velušček, Anton; Turk, Ivan; Dirjec, Janez; Jamnik, Pavel (Arheološki vestnik, 1996)
Lukova Cave is a new Eneolithic site which also contains Pleistocene fauna (the most important being cave lion remains) in southern Slovenia.